Impact behaviour of safety shoe high strength steel parts - Peixinho, Nuno (2018)
This study presents results on the dynamic response of safety toe cap models made of high-strength steel. The structural response to impact loading conditions under normative requirements was properly related to tap the potential of lightweight design for significant reduction of thickness. A fully martensitic steel grade was selected, and numerical models were used to study extensive plastic deformation and strain-rate dependence. Material properties were modelled using the Cowper-Symonds models. The numerical simulation was developed using ANSYS explicit dynamics software and was compared to an experimental standard testing of final prototypes. The numerical modelling approach analysed different friction models seeking to better describe collapsing behaviour. A local stiffening toe cap model with high energy absorption efficiency was validated.